Overcoming Mn-induced chlorosis in sugarcane seedlings by iron - Li, Dongling; Ling, Guizhi; Yang, Shu (Frontiers in Plant Science, 2026)
BackgroundManganese (Mn) toxicity induces severe seedling chlorosis and growth inhibition in sugarcane cultivated on acidic soils, yet the mechanisms driving seasonal recovery and scalable mitigation strategies remain poorly defined. This study aimed to elucidate the role of iron (Fe) deposition from rainwater in natural greening and validate foliar Fe supplementation as an efficient countermeasure.MethodsWe integrated field monitoring across 78 sites, phenological tracking of seasonal recovery, molecular analyses of chlorophyll biosynthesis pathways, and validation experiments (hydroponic and field trials) to investigate Fe-mediated Mn toxicity alleviation. Key metrics included leaf chlorophyll/Fe correlations, gene expression patterns, and agronomic responses to Fe treatments.ResultsField data revealed a strong positive correlation between leaf chlorophyll content and foliar Fe levels (r=0.82, p<0.01). Chlorotic seedlings achieved full visual recovery by late summer, with chlorophyll and Fe concentrations increasing 11.1- and 4.4-fold relative to spring baselines. Mechanistically, Fe reversed Mn-induced functional Fe deficiency by enhancing 5-aminolevulinic acid synthesis (2.3-fold increase) and Mg-protoporphyrin IX monomethyl ester conversion (1.8-fold increase), while downregulating FLUORESCENT expression (60% reduction) and upregulating MgPME cyclase activity (3.1-fold increase). Foliar FeSO₄ applications (0.5–1.5 g Fe L⁻¹) effectively reversed chlorosis, boosting chlorophyll content by 1.9–2.7-fold, seedling survival by 100%, and cane yield by 1.7-fold under Mn-toxic conditions, with minimal input requirements (7.5–22.5 g Fe ha⁻¹).ConclusionOur findings demonstrate that rainwater-borne Fe is a key driver of seasonal recovery from Mn-induced chlorosis in sugarcane. Foliar Fe supplementation emerges as a cost-effective, scalable strategy for mitigating Mn toxicity, offering significant advantages over resource-intensive soil amendments for sustainable sugarcane production on acidic soils.